2023
DOI: 10.1002/ccd.30581
|View full text |Cite
|
Sign up to set email alerts
|

Impact of lesion length on the outcomes of chronic total occlusion percutaneous coronary intervention: Insights from the PROGRESS‐CTO registry

Abstract: Background:The impact of occlusion length on the procedural techniques and outcomes of chronic total occlusion (CTO) percutaneous coronary intervention (PCI) has received limited study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
(29 reference statements)
0
3
1
Order By: Relevance
“…[20][21][22] In addition, in the most recently reported multicenter study on the relationship between lesion length and clinical outcomes, the cut-off for the length of the lesion was set at 20 mm, and the study only reported the association between lesion length and in-hospital or periprocedural outcomes. 23 However, in this study, unlike the results of recent studies that evaluated the role of lesion length on clinical outcomes, the incidence of hard endpoints such as cardiac mortality and mortality were also found to be frequent in long lesions. In addition, we observed that a long lesion was an important independent predictor of overall 5-year adverse clinical outcomes, including cardiac mortality.…”
Section: Cto Lesions Have Different Features Than Non-cto Lesions Incontrasting
confidence: 81%
See 3 more Smart Citations
“…[20][21][22] In addition, in the most recently reported multicenter study on the relationship between lesion length and clinical outcomes, the cut-off for the length of the lesion was set at 20 mm, and the study only reported the association between lesion length and in-hospital or periprocedural outcomes. 23 However, in this study, unlike the results of recent studies that evaluated the role of lesion length on clinical outcomes, the incidence of hard endpoints such as cardiac mortality and mortality were also found to be frequent in long lesions. In addition, we observed that a long lesion was an important independent predictor of overall 5-year adverse clinical outcomes, including cardiac mortality.…”
Section: Cto Lesions Have Different Features Than Non-cto Lesions Incontrasting
confidence: 81%
“…However, including our previous study, none of the studies on lesion length and long‐term prognosis of CTO can demonstrate a correlation between hard endpoints such as cardiac mortality and lesion length 20–22 . In addition, in the most recently reported multicenter study on the relationship between lesion length and clinical outcomes, the cut‐off for the length of the lesion was set at 20 mm, and the study only reported the association between lesion length and in‐hospital or periprocedural outcomes 23 . However, in this study, unlike the results of recent studies that evaluated the role of lesion length on clinical outcomes, the incidence of hard endpoints such as cardiac mortality and mortality were also found to be frequent in long lesions.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations